Análise de controle de força usando servomecanismo eletropneumático - Araujo, Eudes Gonzaga de (2015)
This work presents the designs and results obtained through simulation and experimental testing of conventional controllers P, PI and PID implemented by personal computers applied to an electropneumatic servomechanism for control of force. The system consists of a double acting pneumatic cylinder, which is responsible for applying the force on a mechanical subsystem consisting of a spiral spring, representing the means of working. The proportional electropneumatic flow valve, being the element controlling the flow of compressed air to be released into the pneumatic air cylinder which results in controlled force application; a load cell converts the force applied by the cylinder onto the medium into an electrical signal. The control signal to be applied on the electropneumatic proportional flow valve comes from a signal input and output plate installed on the computer, which is controlled by an algorithm implemented in the computing environment LabVIEW®, wherein the mentioned controllers are inserted, the mathematical representative model of the servomechanism was obtained by applying the parametric identification technique Box-Jenkins (BJ) which results in a family of four models, one of which is chosen to represent the system. The adjustment of the controllers is done by using the critical gain method of Ziegler and Nichols so that the response from the system meets the performance specifications imposed on it. Simulated and experimental results of the system are presented under the inserted controllers, which are analyzed according to relevant theory to the study of conventional controllers; it appears then that the PID controller is best suited for use in its electropneumatic servomechanism.